A Theory of Actions and Habits: The Interaction of Rate Correlation and Contiguity Systems in Free-Operant Behavior - Perez-Riveros, O (American Physical Society, 2020)
Contemporary theories of instrumental performance assume that responding can be controlled by 2 behavioral systems, 1 goal-directed that encodes the outcome of an action, and 1 habitual that reinforces the response strength of the same action. Here we present a model of free-operant behavior in which goal-directed control is determined by the correlation between the rates of the action and the outcome whereas the total prediction error generated by contiguous reinforcement by the outcome controls habitual response strength. The outputs of these two systems summate to generate a total response strength. This cooperative model addresses the difference in the behavioral impact of ratio and interval schedules, the transition from goal-directed to habitual control with extended training, the persistence of goal-directed control under choice procedures and following extinction, among other phenomena. In these respects, this dual-system model is unique in its account of free-operant behavior.